Respuesta :

Answer:

[tex]y^{14} -22y^7+121[/tex]

Step-by-step explanation:

This equation should help:

[tex](a+b)^2=a^2+2ab+b^2[/tex]

[tex](y^{7}-11)^2\\\\=y^{14} +2*y^7*-11+11^2\\\\=y^{14} -22y^7+121[/tex]

Answer:

[tex] {y}^{14} - 22 {y}^{7} + 121[/tex]

Step-by-step explanation:

[tex](y {}^{7 } - 11)( {y}^{7} - 11)[/tex]

First terms,

[tex]{y}^{14} [/tex]

Outer,

[tex] {y}^{7} \times - 11 = - 11 {y}^{7} [/tex]

Inner,

[tex] {y}^{7} \times - 11 = - 11 {y}^{7} [/tex]

Last,

[tex] - 11 \times - 11 = 121[/tex]

Add all terms up

[tex] {y}^{14} - 22 {y}^{7} + 121[/tex]